2004
DOI: 10.1152/japplphysiol.01331.2003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in neutrophil surface receptor expression, degranulation, and respiratory burst activity after moderate- and high-intensity exercise

Abstract: Intense exercise stimulates the systemic release of a variety of factors that alter neutrophil surface receptor expression and functional activity. These alterations may influence resistance to infection after intense exercise. The aim of this study was to examine the influence of exercise intensity on neutrophil receptor expression, degranulation (measured by plasma and intracellular myeloperoxidase concentrations), and respiratory burst activity. Ten well-trained male runners ran on a treadmill for 60 min at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
87
4
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 35 publications
14
87
4
4
Order By: Relevance
“…Several studies have reported that exercise increases neutrophil degranulation, as indicated by elevated plasma concentrations of elastase and myeloperoxidase (Peake, 2002;Peake et al, 2004;Suzuki et al, 2003). More recent studies have also observed that plasma calprotectin concentration is elevated after exercise (Fagerhol, Nielsen, Vetlesen, Sandvik, & Lyberg, 2005;Mooren et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that exercise increases neutrophil degranulation, as indicated by elevated plasma concentrations of elastase and myeloperoxidase (Peake, 2002;Peake et al, 2004;Suzuki et al, 2003). More recent studies have also observed that plasma calprotectin concentration is elevated after exercise (Fagerhol, Nielsen, Vetlesen, Sandvik, & Lyberg, 2005;Mooren et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that activated neutrophils increase oxidant burden and exacerbate disease via production of reactive oxygen and nitrogen species (30,31,46). Therefore, to further evaluate the role neutrophils in the context of oxidant Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in neutrophil MPO concentration after exercise is accompained by an increase in plasma MPO. Changes in plasma MPO concentration seems to depend on exercise intensity [47]. Secreted MPO is also rapidly deactivated in plasma, losing its catalytic activity.…”
Section: Discussionmentioning
confidence: 99%